Perilaku Komunikasi Mahasiswa selama Mengikuti Pembelajaran Daring di Era Covid-19 - Lidia Djuhardi (Journal on Education, 2023)
Learning during the Covid-19 pandemic era was mostly carried out using digital devices and various applications such as Gadgets, Podcasts, Blogs, Videos and so on. Learning in the Covid-19 era is known as Online learning. The problem is, online learning has many pros and cons. This research aims to find out the students' experiences, how they interpret these experiences and the behaviors that are expressed both verbally and non-verbally. This study uses an interpretive paradigm with phenomenological methods, the theory used by Alfred Schutz's phenomenology. The research informants were undergraduate students at UPI YAI majoring in Communication Studies class of 2019 to 2022. The results of this research found that the experience of students while doing online learning had a positive tendency, where they were happy and liked learning for various reasons such as more effective time, cheaper costs, and more bravery. In line with their experience they interpret it as relaxed, interactive, and homi [family] learning, which is revealed from their behavior, no need for preparation and relaxed.